2020
DOI: 10.1038/s41598-020-71247-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the upward curvature of toe springs on walking biomechanics in humans

Abstract: Although most features of modern footwear have been intensively studied, there has been almost no research on the effects of toe springs. This nearly ubiquitous upward curvature of the sole at the front of the shoe elevates the toe box dorsally above the ground and thereby holds the toes in a constantly dorsiflexed position. While it is generally recognized that toe springs facilitate the forefoot’s ability to roll forward at the end of stance, toe springs may also have some effect on natural foot function. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 49 publications
(58 reference statements)
3
14
0
Order By: Relevance
“…The first MTPJ in the sagittal plane was significantly reduced in the shod condition, which was consistent with previous studies ( Lin et al, 2013 ; Wegener et al, 2015 ; Sichting et al, 2020 ). Specifically, Wegener et al (2015) found that shoes reduced the first MTPJ’s peak EX during running from 31.5° (barefoot) to 12.6° (shod), and Sichting et al (2020) found that the EX ROM of the first MTPJ decreased from 27.9 (barefoot) to 19.7 (shod). The minimum EX angle of the first MTPJ in the shod condition was significantly increased.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The first MTPJ in the sagittal plane was significantly reduced in the shod condition, which was consistent with previous studies ( Lin et al, 2013 ; Wegener et al, 2015 ; Sichting et al, 2020 ). Specifically, Wegener et al (2015) found that shoes reduced the first MTPJ’s peak EX during running from 31.5° (barefoot) to 12.6° (shod), and Sichting et al (2020) found that the EX ROM of the first MTPJ decreased from 27.9 (barefoot) to 19.7 (shod). The minimum EX angle of the first MTPJ in the shod condition was significantly increased.…”
Section: Discussionsupporting
confidence: 93%
“…Human metatarsal heads are dorsally oriented and mediolaterally broad articular surfaces. The dorsally oriented metatarsal heads in the human forefoot are thought to increase the range of EX motion at the MTPJ by providing more dorsal articular surface area on which the proximal phalangeal base can slide ( Fernandez et al, 2016 ; Sichting et al, 2020 ) In the current study, the EX trend of the first MTPJ was consistent with the superior/inferior translation trend, which further supported the result of the previous study ( Phillips et al, 1996 ). The shoe limited the flexion and extension of the first MTPJ, thus reducing the ROM of joint translation in the sagittal plane.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As regular use of minimal footwear was the only intervention introduced in our study, and the control group showed no changes, it must be concluded that daily activity in minimal footwear increases foot strength for healthy adults, confirming our second hypothesis. Mechanistically, this is probably due to the lower bending stiffness of minimal shoes compared to conventional shoes, which are typically harder to flex about the MPJ, and may also be part explained by the absence of a structural toe spring which has been suggested to weaken the foot 47 . This stiffness contributes to the resistive force required for the foot to be a stiff lever upon push-off, thereby reducing the demand on the foot muscles during gait.…”
Section: Discussionmentioning
confidence: 99%
“…As regular use of minimal footwear was the only intervention introduced in our study, and the control group showed no changes, it must be concluded that daily activity in minimal footwear increases foot strength for healthy adults, confirming our second hypothesis. Mechanistically, this is probably due to the lower bending stiffness of minimal shoes compared to conventional shoes, which are typically harder to flex about the MPJ, and may also be part explained by the absence of a structural toe spring which has been suggested to weaken the foot 47 . This stiffness contributes to the resistive www.nature.com/scientificreports/ force required for the foot to be a stiff lever upon push-off, thereby reducing the demand on the foot muscles during gait.…”
Section: Discussionmentioning
confidence: 99%